EXPLORING THE SOCIOCULTURAL SIGNIFICANCE OF LANGSTON HUGHES’ POETRY - Umirzoqova Shaxrizoda Mirxalil qizi; Khamitov Eldorbek Erkin o'g'li (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract: Langston Hughes, a central figure in American literature and the Harlem Renaissance, left an indelible mark through his poetry, which serves as a mirror reflecting the sociocultural landscape of his time. This article delves into the multifaceted dimensions of Hughes' poetry, analyzing its historical context, thematic elements, and enduring relevance. Through a sociocultural lens, this study elucidates the ways in which Hughes' poetry captures the complexities of race, identity, and social justice, offering valuable insights into the human experience.